2013
DOI: 10.3390/ijms141122544
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Acyloxycyclohexylsulfonamides and Evaluation on Their Fungicidal Activity

Abstract: Eighteen N-substituted phenyl-2-acyloxycyclohexylsulfonamides (III) were designed and synthesized by the reaction of N-substituted phenyl-2-hydroxyl-cycloalkylsulfonamides (I, R1) with acyl chloride (II, R2) in dichloromethane under the catalysis of TMEDA and molecular sieve. High fungicidal active compound N-(2,4,5-trichlorophenyl)-2-(2-ethoxyacetoxy) cyclohexylsulfonamide (III-18) was screened out. Mycelia growth assay against the Botrytis cinerea exhibited that EC50 and EC80 of compound III-18 were 4.17 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Substituent benzoyl chlorides ( III- 1~ III- 17), acetyl chlorides ( III- 18~ III- 23), halogenated acetyl chlorides ( III- 24~ III- 27), alkoxylacetyl chlorides ( III- 28~ III -29) were synthesized according to the given method in the ref. 32 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substituent benzoyl chlorides ( III- 1~ III- 17), acetyl chlorides ( III- 18~ III- 23), halogenated acetyl chlorides ( III- 24~ III- 27), alkoxylacetyl chlorides ( III- 28~ III -29) were synthesized according to the given method in the ref. 32 .…”
Section: Methodsmentioning
confidence: 99%
“…In vitro effects of compounds against B. cinerea were evaluated by mycelium growth rate method 30 31 32 . The tested compounds were dissolved in DMSO (dimethyl sulfoxide) and mixed with sterile molten potato dextrose agar (PDA) to a final concentration of 50 mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, different scaffolds were introduced onto lead 2-oxocycloalkyl-sulfonamides, and the structure-activity relationships (SAR) were studied [ 29 , 30 , 31 , 32 ]. According to the results and following a program of extension and change of these compounds’ structures, we changed the naphthenic group linked with the sulfur bond in the sulfonamide group into an alkyl chain and found that the ethylsulfonamide group was the essential bioactive moiety and therefore, the ethylsulfonamide group was identified as a key building block for compound activity.…”
Section: Introductionmentioning
confidence: 99%
“…Research in heterocyclic chemistry has gained thrust in recent times because more than half of the biologically active molecules belong to various classes of heterocycles [1][2][3][4][5][6][7][8] . 1, 3-Diaza-heterocycles like pyrimidine and quinazoline derivatives, quinazolinones in particular, have been identified as potential drug molecules against various types of diseases.…”
Section: Introductionmentioning
confidence: 99%